2021
DOI: 10.1055/s-0041-1740213
|View full text |Cite
|
Sign up to set email alerts
|

Urinary N-terminal Pro-Brain Natriuretic Peptide in Newborn Infants with Cardiac and Pulmonary Diseases

Abstract: Objectives The aim of this study was to assess the feasibility of urinary N-terminal pro-brain natriuretic peptide (NT-proBNP) as noninvasive screening tool for congenital heart diseases in full-term neonates with respiratory distress. Study Design A prospective cohort study was conducted on 90 full-term infants. Newborn were assigned into three groups: pulmonary, cardiac, and control groups. Urinary NT-proBNP were measured in all studied groups at day 1 (NT-proBNP1) and day 5 (NT-proBNP5). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Several studies have demonstrated that NT‐proBNP levels are detectable in the urine of preterm newborns with significant associations between elevated urinary NT‐proBNP concentrations and neonatal morbidities such as hs‐PDA, retinopathy of prematurity, and BPD with pulmonary hypertension 12–14,18 . Urinary NT‐proBNP also seems promising as a screening tool for CHD in term newborns and has shown potential to differentiate simple and complex CHD 11,19 . Furthermore, urinary‐NT‐proBNP would be helpful in the pediatric ambulatory setting to assess heart failure when combined with clinical scores 20 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated that NT‐proBNP levels are detectable in the urine of preterm newborns with significant associations between elevated urinary NT‐proBNP concentrations and neonatal morbidities such as hs‐PDA, retinopathy of prematurity, and BPD with pulmonary hypertension 12–14,18 . Urinary NT‐proBNP also seems promising as a screening tool for CHD in term newborns and has shown potential to differentiate simple and complex CHD 11,19 . Furthermore, urinary‐NT‐proBNP would be helpful in the pediatric ambulatory setting to assess heart failure when combined with clinical scores 20 .…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14]18 Urinary NT-proBNP also seems promising as a screening tool for CHD in term newborns and has shown potential to differentiate simple and complex CHD. 11,19 Furthermore, urinary-NT-proBNP would be helpful in the pediatric ambulatory setting to assess heart failure when combined with clinical scores. 20 Like these populations, obtaining blood samples for testing in acute bronchiolitis is technically challenging for the healthcare provider and stressful and painful for the patient, especially in cases where repeated tests are needed for monitoring evolution.…”
Section: Feasibility Of Urinary Nt-probnp In Acute Bronchiolitismentioning
confidence: 99%
“…These investigations have reported significant associations between elevated urinary NT-proBNP concentrations and neonatal morbidities such as hemodynamically significant persistent ductus arteriosus, retinopathy of prematurity, and bronchopulmonary dysplasia with pulmonary hypertension [12,14,18,19]. Urinary NT-proBNP also seems promising as a screening tool for congenital heart diseases in newborns and has shown potential to differentiate simple and complex CHD [11,20]. Recently, urinary-NT-proBNP has been helpful in the pediatric ambulatory setting to assess heart failure in children with congenital heart diseases when combined with clinical scores [21].…”
Section: Feasibility Of Urinary Nt-probnp In Acute Bronchiolitismentioning
confidence: 99%